SEJARAH PEMIKIRAN EKONOMI NEO-KLASIK,KAPITALISME, SOSIALISME, DAN KEYNESIAN - Muhammad Satrio Juliyanto; Rafi Alkaf Asy Syafi; Muh Fatkhurrozi; Muhammad Taufiq Abadi; Muhammad Aris Syafi’i (CV. KAMPUS AKADEMIK PUBLISING, 2024)
A number of important economic theories have shaped the evolution of the global economy. The neo-classical theory derives from the classic theory, which emphasizes the importance of free markets and private ownership in managing the economy. as a major pillar, enabling significant economic growth but resulting in inequality. On the contrary, socialist ideology emphasizes group resource ownership and a fairer distribution. This system aims to reduce the disparities created by capitalism. However, socialist practices are very diverse and often involve market planning and market elements. Keynesianism emerged as a response to the Great Depression and focused on the way governments controlled the economy through monetary and fiscal policies to economic stability. In short, neo-classicism, capitalism, socialism, and Keynesianism greatly influenced the development of the global economic system.